2004
DOI: 10.1073/pnas.0407009101
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling reveals how interplay between components of a GTPase-cycle module regulates signal transduction

Abstract: Heterotrimeric G protein signaling is regulated by signaling modules composed of heterotrimeric G proteins, active G proteincoupled receptors (Rs), which activate G proteins, and GTPaseactivating proteins (GAPs), which deactivate G proteins. We term these modules GTPase-cycle modules. The local concentrations of these proteins are spatially regulated between plasma membrane microdomains and between the plasma membrane and cytosol, but no data or models are available that quantitatively explain the effect of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 49 publications
(58 reference statements)
8
53
0
Order By: Relevance
“…For G-protein activation we then calculate range for k + of 10 −6 to 10 −3 (#/cell) −1 sec −1 . This range overlaps with observed values of k f (10 −7 (#/cell) −1 sec −1 to 10 −4 (#/cell) −1 sec −1 (Bornheimer et al, 2004;Simons et al, 2004;Yi et al, 2003)). This broad range of values for k f is likely due to the differences in the cell types used and the concentrations of the receptors and G-proteins in these experiments.…”
Section: Estimating the Role Of Diffusionsupporting
confidence: 86%
“…For G-protein activation we then calculate range for k + of 10 −6 to 10 −3 (#/cell) −1 sec −1 . This range overlaps with observed values of k f (10 −7 (#/cell) −1 sec −1 to 10 −4 (#/cell) −1 sec −1 (Bornheimer et al, 2004;Simons et al, 2004;Yi et al, 2003)). This broad range of values for k f is likely due to the differences in the cell types used and the concentrations of the receptors and G-proteins in these experiments.…”
Section: Estimating the Role Of Diffusionsupporting
confidence: 86%
“…Several models also shed light on additional mechanisms that may limit cross-talk. Bornheimer et al (8) suggested that clustering/coupling interactions between receptor, G-protein, and/or RGS proteins could offer such physical scaffolding. Alternatively, Zhong et al (52) showed that the membrane level "spread" of G-protein signaling could be limited by a kinetic scaffolding mechanism in which RGS proteins, by their acceleration of GTP hydrolysis, reduce depletion of local (near the receptor) G␣ GTP levels enough to allow rapid recoupling of G-protein to receptor.…”
Section: New Ideas On Cross-talk and Dimerizationmentioning
confidence: 99%
“…For example, models of GPCR signaling may include vast detail in the G-protein activation/ deactivation cycle (8) or may have no explicit inclusion of G-proteins at all but rather lump their effect into what happens to a downstream component. In other words, there is a choice as to how fine-or coarse-grained you make your model.…”
Section: Model Developmentmentioning
confidence: 99%
“…This has the effect of increasing the pool of active G-proteins in the vicinity of receptors, while keeping G-protein activity low elsewhere. In another study Bornheimer et al (2004) provided a theoretical analysis of the 7TMR-G protein-RGS cycle. They studied signal propagation under various relative concentrations of active receptor, G protein and RGS protein.…”
Section: Dynamic Regulation Of Signaling Pathwaysmentioning
confidence: 99%